2010
DOI: 10.1007/s00431-010-1337-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of children with group A streptococcal toxic shock syndrome admitted to pediatric intensive care units

Abstract: STSS is a very severe condition secondary to invasive GAS infection. It can occur at any age, but especially in young children. Due to the lack of specific symptoms and signs and its very rapid progression to shock and organ dysfunction, pediatricians and emergency physicians must be aware of this possibility and immediately initiate aggressive treatment when suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
3
14
0
5
Order By: Relevance
“…The association of staphylococcal TSS with tampon use and breach of skin integrity, and streptococcal TSS with acute lower respiratory infection and varicella infection, is also consistent with previous reports 4 7 15. Streptococcal TSS has been reported to complicate close to 10% of hospitalised varicella cases, and in one series, >20% of streptococcal TSS followed varicella infection 4 6 16. The few cases of varicella-associated TSS in our study may be explained by the universal varicella vaccine programme that was introduced in Victoria in 2005 17…”
Section: Discussionsupporting
confidence: 89%
“…The association of staphylococcal TSS with tampon use and breach of skin integrity, and streptococcal TSS with acute lower respiratory infection and varicella infection, is also consistent with previous reports 4 7 15. Streptococcal TSS has been reported to complicate close to 10% of hospitalised varicella cases, and in one series, >20% of streptococcal TSS followed varicella infection 4 6 16. The few cases of varicella-associated TSS in our study may be explained by the universal varicella vaccine programme that was introduced in Victoria in 2005 17…”
Section: Discussionsupporting
confidence: 89%
“…TSS is caused by toxin-producing strains of Staphylococcus aureus or Streptococcus pyogenes and occurs in both adult and pediatric patients ( 1 5 ). TSS remains a rare but severe disease, with a mortality rate that varies from 4 to 27% for streptococcal (Str) TSS ( 2 4 ) and from 0 to 22% for menstrual and non-menstrual staphylococcal (Sta) TSS ( 1 ). Studies conducted in pediatric intensive care units (PICU) reported a mortality rate that can reach 25% for Str-TSS ( 2 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…TSS remains a rare but severe disease, with a mortality rate that varies from 4 to 27% for streptococcal (Str) TSS ( 2 4 ) and from 0 to 22% for menstrual and non-menstrual staphylococcal (Sta) TSS ( 1 ). Studies conducted in pediatric intensive care units (PICU) reported a mortality rate that can reach 25% for Str-TSS ( 2 6 ). The outcome of Sta-TSS is more favorable in children than in adults ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group A Streptococcus causes a severe illness with similarities to the staphylococcal toxic shock syndrome, occurring in both children and adults, associated with invasive group A streptococcal disease [33]. Patients with this syndrome present acutely with high fever, erythematous rash, mucous membrane involvement, hypotension, and multiorgan failure [34,35]. Unlike staphylococcal Pediatric Nephrology DOI 10.1007/978-3-642-27843-3_47-1 # Springer-Verlag Berlin Heidelberg 2014 toxic shock syndrome, in which the focus of infection is usually trivial and bacteremia is seldom seen, the streptococcal toxic shock syndrome is usually associated with bacteremia or a serious focus of infection such as septic arthritis, myositis, or osteomyelitis.…”
Section: Staphylococcus Aureusmentioning
confidence: 99%